I found this simplification, but I'm not understanding how they came up with mn - 3n simplify: 2m^2n - 6mn ____________ 2m = 2m^2n - 6mn ______ ______ 2m 2m = mn - 3n
Follow Math Help Forum on Facebook and Google+
Hello hansfordmc Originally Posted by hansfordmc I found this simplification, but I'm not understanding how they came up with mn - 3n simplify: 2m^2n - 6mn ____________ 2m = 2m^2n - 6mn ______ ______ 2m 2m = mn - 3n Grandad
I wish they would have explained it like that - thanks so much.
View Tag Cloud